Perceptions and attitudes towards genetic engineering of oil palm and its produce in Malaysia: a review / Hanie Suraiya Hadzri - Hadzri, Hanie Suraiya (Faculty of Plantation and Agrotechnology, 2018)
The speedy demand of world using vegetable oils and fats in daily life, it is very essential for people to using oil and the demand of using vegetable oil are increased year by year. Oil palm does has big potential to increase the demands of vegetable oils and fats. Country need to cultivate the oil palm to meet the demand of using vegetable oils and fats. Oil palm is the most important oil crop in the world that produce higher oil than other oil crops. To meet challenge of high demand of vegetable oil and fats, the production of palm oil should be increased. Forest are importance and its preservation must be considered. We need to plant the oil palm with minimal area but with high yield. A possibility of developing a high yielding oil palm should be explore by using genetic information derived from oil-palm genome. Hence, this review will help people out there to enhance their perception and attitudes about genetic engineering in Malaysia and hope that Malaysian will be more concerned about biotechnology to build modern biotechnology in our country and genetic engineering will improve and increased the production of high quality oil palm.